Dilema Sosial Pengguna Transportasi Jakarta: Survai Penilaian dan Niat Menggunakan Transportasi Publik di Jakarta - Vincentius Rachmadi Parmono (Universitas Katolik Indonesia Atma Jaya, 2018)
The traffic problem in Jakarta can be seen as a social dilemma problem. The commuter here face the dilemma to decide to commute by private or public transportation. This decision situation reveals the conflict between immediate self interest and longterm collective interest. The goal of this reseach is twofold. First, the research elaborrate the differences in the level of interest of among the commuter in the transportation modes. Second, the research analyse the influence of social dilemma awareness of the commuter to prioritize the common interest of the commuter. The first reseach question is answered by employing descriptive analysis and the second one is analyzed by inferential analysis. The results of this research reveals some important points. First, the commuter think that the congestion is the most traffic problem in Jakarta. Second, private transportation is preferred transportation mode than public transportation. Third, the commuter intention to prioritize public transportation is influenced by three factors, i.e. flexibility, low fare, speed (short duration).